2016
DOI: 10.1097/md.0000000000003282
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term and Interactive Effects of Pay-For-Performance Interventions among Diabetic Nephropathy Patients at the Early Chronic Kidney Disease Stage

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…A meta-analysis of early versus late referrals to nephrologists indicated a significantly higher overall mortality, longer hospital stay, and early at the time of renal replacement therapy initiation in the late referrals compared with the early referrals 42 . It was previously reported in a study of 32,084 early CKD patients from the NHIRD in Taiwan that an early CKD P4P intervention resulted in a significantly better prognosis in all-cause mortality among matched participants in both P4P programs 43 . Furthermore, the analysis of advanced CKD cases in the present study confirmed that the P4P program for pre-ESRD care education is a crucial tool to improve survival and patient outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis of early versus late referrals to nephrologists indicated a significantly higher overall mortality, longer hospital stay, and early at the time of renal replacement therapy initiation in the late referrals compared with the early referrals 42 . It was previously reported in a study of 32,084 early CKD patients from the NHIRD in Taiwan that an early CKD P4P intervention resulted in a significantly better prognosis in all-cause mortality among matched participants in both P4P programs 43 . Furthermore, the analysis of advanced CKD cases in the present study confirmed that the P4P program for pre-ESRD care education is a crucial tool to improve survival and patient outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, we need more evidence-based studies on the long term outcome of P4P programs to convince primary care physicians to participate in P4P programs for quality improvement in healthcare. Using diabetic care as an example, in Taiwan, most related studies show that diabetes P4P programs result in favorable outcome in process (examining HbA1C, LDL), patient outcome (decreasing mortality, nephropathy, and cost-effectiveness analyses) [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is now regarded as one of the most challenging public health problems worldwide 1 . Both the economic burden and loss of health caused by complications of DM indicate the importance of primary prevention and early intervention in the management of DM 2 , 3 . Diabetic retinopathy (DR) is a common microvascular complication of DM and a major preventable cause of visual impairment in the working-age population 4 .…”
Section: Introductionmentioning
confidence: 99%